Remediation of contaminated marine sediment using bentonite, kaolin and sand as capping materials - Kabir Aliyu, Mohammed (2019)
There is a growing public concern over the issue of sediment contamination resulting from industrial, municipal wastewater, mining activities, and improper use of chemical fertilizer or pesticides. The conventional treatment of contaminated sediment is dredging, but this treatment is expensive and requires a large area of land for disposal. In situ capping of contaminated sediment is considered as a cheaper technique compared to dredging and efficient treatment technology to immobilize pollutants in sediments on site. In this technique, sediments are capped by placing a layer of inert materials like sand, clean soil, or gravel or active materials like activated carbon, zeolite, or apatite over sediments in order to reduce the risk to the aquatic environment. The objective of this study is to determine the effectiveness of using active materials; bentonite (B), kaolin (K), mixture of bentonite with kaolin (1:1) (BK) as capping materials to block the release of five heavy metals (Pb, Cr, Cu, Cd and Zn) from artificially polluted sediments. The effectiveness of B, K, and BK for preventing the leachability of the trace metals was assessed on a bench-scale laboratory experiment in glass tanks for 90 days, where 1cm thick layer of capping material and sand was placed above the contaminated sediment. The results showed that B and BK reduced the leachability of Pb, Cr, and Cu from the sediments. The results also showed that B and BK could be used as potential capping materials for the remediation of contaminated sites due to their significant entrapping of Pb, Cu, and Cr. The pollutants were released into the overlying water from the contaminated sediment in the following decreasing order; Cd > Zn > Pb > Cu > Cr. The adsorption kinetics analysis also showed that the process of adsorption was by chemisorption. This study proved that bentonite and mixture of bentonite with kaolin clays covered with sand could be used as capping materials for in situ treatment of Pb, Cu, Cr, Zn, and Cd for contaminated marine sediment.